Critical amplitudes and mass spectrum of the 2d Ising model in a magnetic field - Caselle, M.; Hasenbusch, Martin (Nuclear physics. B, Particle physics, 2000)
We compute the spectrum and several critical amplitudes of the two-dimensional Ising model in a magnetic field with the transfer matrix method. The three lightest masses and their overlaps with the spin and the energy operators are computed on lattices of a width up to L1=21 . In extracting the continuum results we also take into account the corrections to scaling due to irrelevant operators. In contrast with previous Monte Carlo simulations our final results are in perfect agreement with the predictions of S-matrix and conformal field theory. We also obtain the amplitudes of some of the subleading corrections, for which no S-matrix prediction has yet been obtained.